从“花园城市”到“花园中的城市” : 新加坡环境政策的理念与实践及其对中国的启示 = From “Garden city” to “A city in a garden” : the ideals and practices of Singapore’s environmental greenery policy and its implications for the Chinese government - 王君 Wang, Jun (2015)
本文主要梳理新加坡从“花园城市”到“花园中的城市”环境绿化发展历程，探讨政府在此过程中的理念和政策执行机制，并以“滨海南”综合功能发展区为例，分析新加坡的理念与政策配套如何实施，建立城市治理的新模式，从而打造世界级“花园中的城市”，最后得出对中国相关城市的借鉴。This article has five sections. First, it introduces the policy evolution from “Garden City” to “City in A Garden”; secondly, we discuss the government’s conceptualization of the policy; thirdly, it explores various mechanisms that are used by the government to implement the “Garden City” and “City in A Garden” policies; fourthly, we use “Marina South” mixed-use residential district as an example to demonstrate how the policy is put into implementation. This paper concludes with some discussions on the policy implications for the Chinese government.